2018
DOI: 10.1016/j.asr.2017.10.033
|View full text |Cite
|
Sign up to set email alerts
|

A study of acoustic halos in active region NOAA 11330 using multi-height SDO observations

Abstract: We analyze data from the Helioseismic Magnetic Imager (HMI) and the Atmospheric Imaging Assembly (AIA) instruments on board the Solar Dynamics Observatory (SDO) to characterize the spatio-temporal acoustic power distribution in active regions as a function of the height in the solar atmosphere. For this, we use Doppler velocity and continuum intensity observed using the magnetically sensitive line at 6173Å as well as intensity at 1600Å and 1700Å. We focus on the power enhancements seen around AR 11330 as a fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…These enhanced emissions were subsequently confirmed extending up to chromospheric heights (Braun et al, 1992;Toner and Labonte, 1993) but were absent in measurements of the continuum intensity (Hindman and Brown, 1998;Jain and Haber, 2002). With the availability of multi-height observations from Solar Dynamics Observatory (SDO; Pesnell et al, 2012), several studies showed the presence of intensity halos in different spectral lines but at higher heights (Moretti et al, 2007;Schunker and Braun, 2011;Howe et al, 2012;Tripathy et al, 2012;Rajaguru et al, 2013;Tripathy et al, 2018). Figure 3 shows the power maps for AR 11092 in different frequency bands and at different heights of the solar atmosphere corresponding to different observables (Tripathy et al, 2012).…”
Section: Power Absorption and Acoustic Emissionsmentioning
confidence: 91%
“…These enhanced emissions were subsequently confirmed extending up to chromospheric heights (Braun et al, 1992;Toner and Labonte, 1993) but were absent in measurements of the continuum intensity (Hindman and Brown, 1998;Jain and Haber, 2002). With the availability of multi-height observations from Solar Dynamics Observatory (SDO; Pesnell et al, 2012), several studies showed the presence of intensity halos in different spectral lines but at higher heights (Moretti et al, 2007;Schunker and Braun, 2011;Howe et al, 2012;Tripathy et al, 2012;Rajaguru et al, 2013;Tripathy et al, 2018). Figure 3 shows the power maps for AR 11092 in different frequency bands and at different heights of the solar atmosphere corresponding to different observables (Tripathy et al, 2012).…”
Section: Power Absorption and Acoustic Emissionsmentioning
confidence: 91%
“…The variation of acoustic power in active regions may have significant effects on inferences of subsurface flows, because the suppression of acoustic sources in magnetized regions causes anisotropy in wave propagation properties. Since halos have been seen at many different heights of the solar atmosphere (Rajaguru et al 2013;Tripathy et al 2018), these questions again emphasize the need for multi-height observations.…”
Section: Acoustic Halosmentioning
confidence: 99%